Peran Assurance atas Sustainability Disclosure dalam Meningkatkan Kredibilitas Informasi Akuntansi dan Nilai Perusahaan pada Emiten Non-Keuangan di Indonesia - Berlin Barus; Bibella Rosyanti Kristiani Hutasoit; Harlen Silalahi; Dumariani Silalahi (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The issue of sustainability disclosure is increasingly important in the capital market because it is used by investors to assess a company's long-term performance. However, the narrative, voluntary, and minimally standardized nature of disclosure raises doubts about the credibility of the information presented. This situation drives the need for an assurance mechanism to increase trust and reduce information asymmetry. Based on these issues, this study aims to analyze the role of assurance on sustainability disclosure in enhancing the credibility of accounting information and firm value in non-financial issuers in Indonesia. The study uses a quantitative approach with panel data of non-financial issuers listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was determined through purposive sampling and analyzed using fixed-effect panel data regression with robust standard errors. The results show that sustainability disclosure has a positive effect on the credibility of accounting information and firm value. Furthermore, assurance has been shown to have a positive effect and strengthen this relationship. These findings indicate that the market considers not only the extent of sustainability disclosure but also the existence of external assurance. This study confirms the role of assurance as a mechanism for increasing trust and the value relevance of sustainability information in investment decisions.